2013
DOI: 10.1371/currents.outbreaks.7735b392bdcb749baf5812d2096d331e
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Significant Levels of Toxigenic V. cholerae O1 in the Haitian Aquatic Environment During the 2012 Rainy Season

Abstract: Background: On October 21, 2010, Haiti was struck by a cholera epidemic for the first time in over a century. Epidemiological and molecular genetic data have clearly demonstrated that the bacterium was imported. Nevertheless, the persistence of the epidemic for more than two years, the high incidence rates in some coastal areas and the seasonal exacerbations of the epidemic during the rainy seasons have prompted us to examine the levels of toxigenic Vibrio cholerae in the Haitian aquatic environment. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The temporal and spatial variation in collection is consistent with wider diffusion of this strain in Haitian waterways. However, despite ongoing aquatic environment monitoring for toxigenic V. cholerae by at least four groups461516, it is difficult to assess the true prevalence of this non-toxigenic O1 lineage in Haitian aquatic environment since the focus has largely been on identifying toxigenic strains. Genetic analysis showed that both were cholera-toxin ( ctx ) negative O1 strains and were positive for ompW , toxR , and tcpA CL6 .…”
Section: Resultsmentioning
confidence: 99%
“…The temporal and spatial variation in collection is consistent with wider diffusion of this strain in Haitian waterways. However, despite ongoing aquatic environment monitoring for toxigenic V. cholerae by at least four groups461516, it is difficult to assess the true prevalence of this non-toxigenic O1 lineage in Haitian aquatic environment since the focus has largely been on identifying toxigenic strains. Genetic analysis showed that both were cholera-toxin ( ctx ) negative O1 strains and were positive for ompW , toxR , and tcpA CL6 .…”
Section: Resultsmentioning
confidence: 99%
“…However, other researchers, using only culture methods, did not isolate or detect toxigenic V. cholerae from water samples collected in July 2012 from 36 aquatic locations in the Ouest and Artibonite Departments. 35 Non-toxigenic V. cholerae non-O1/O139 isolates that were tcpA-positive were repeatedly recovered from the River 3 site in the Artibonite Department during the surveillance project. The tcpA gene encodes the major subunit of the toxin co-regulated pilus (TCP), the receptor for lysogenic bacteriophage (CTXΦ) carrying cholera toxin genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two other environmental studies were staged after the peak of the epidemic. The first attested the detection of toxigenic V. cholerae in 3 out of 179 samples (Alam et al 2014), while the other found none (Baron et al 2013). The absence of clear evidence of an established environmental community of toxigenic V. cholerae, supported by detailed field investigations, led some authors to conclude that the transmission cycle of the disease is being maintained by bacteria freshly shed by infected individuals ) and thus that the disease could possibly be eradicated.…”
Section: Introductionmentioning
confidence: 99%